The role of knowledge management at BSIP TAS Malang in improving public sector performances - Selma Kendida Arsy; Bambang Supriyono; I Gede Eko Putra Sri Sentanu (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to improve civil servant training performance from a knowledge management (KM) perspective in the context of BSIP TAS's transition from a research institution to a standardization agency. Methodology/Approach: A descriptive qualitative approach was employed, utilizing observation, in-depth interviews, and documentation. KM strategies were mapped using Dalkir’s framework, which includes knowledge audit, gap analysis, and the development of a strategy roadmap. Results/Findings: The findings indicate that BSIP TAS has begun implementing KM through need-based training and informal peer mentoring. However, challenges persist in terms of uneven knowledge distribution and the lack of systematic documentation. Conclusions: To enhance training performance and prevent knowledge loss, BSIP TAS must strengthen its KM practices by adopting digital systems, formalizing archiving processes, and establishing structured knowledge-sharing forums. These initiatives are crucial for sustainable organizational performance. Limitations: The study is limited to qualitative data from a single institution in transition, which may affect the generalizability of findings to other organizational contexts. Contribution: This study advances the KM literature by uniquely applying Dalkir’s framework to a government agency undergoing transformation, providing novel theoretical and practical insights into how tailored KM strategies can optimize performance and preserve critical knowledge amidst institutional change.